The perennial problem: a critical analysis of the income versus capital distinction in respect of share transactions in the new "Digital" economy - Juric,DF (Department of Commercial Law, 2023)
This dissertation will examine the application of the test used to distinguish income from capital in South African Income Tax law and critically analyse the problems associated therewith. Such problems relate to the nature of a receipt or accrual upon the disposal of an asset as well as a range of other receipts and accruals including royalties, compensation, interest, rental and foreign exchange gains. The scope of this dissertation will be limited to an analysis of the problems of application in respect of the disposal of an asset, more specifically the case of share transactions on the Johannesburg Stock Exchange in the light of the development of the new or "digital economy". Following such an analysis of the inherent problems of the test as currently applied by courts in South Africa to such a situation, a brief summary is given of the legislative and other attempts made to resolve such a problem. The effectiveness of such solutions is further examined, particularly the proposed capital gains tax in the light of the experience of other comparative tax jurisdictions in dealing with the problem. Finally two suggested solutions are outlined to the problem, the acceptance of which it is contended will depend on the weighing up of the competing values of certainty versus equity in the South African tax environment at any given time.